Analisis Pola Asuh dan Spiritualitas Orang Tua terhadap Resiliensi Emosional Siswa dalam Menghadapi Tekanan Akademik di Sekolah Islam Terpadu - Aziz, Abdul; Endang Sumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the mechanisms and impacts of parents’ spirituality-based parenting on students’ emotional resilience in facing academic pressure. The background of this study is based on the increasing phenomenon of academic stress and the important role of spiritual parenting in shaping students’ character and mental resilience. This research employed a qualitative approach with a phenomenological design conducted at SMPIT Al Wakil. The research subjects included parents, students, and teachers selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using the Miles, Huberman, and Saldana model. The results indicate that spirituality-based parenting positively influences students’ emotional resilience. Students who receive spiritual habituation within the family tend to be better at managing emotions, remain calmer in dealing with academic pressure, and demonstrate more patience and responsibility. Parental role modeling and non-pressuring parenting practices are key factors in shaping these outcomes. In addition, schools contribute by reinforcing spiritual values through character-building programs. However, limited family communication remains a constraint affecting students’ openness. This study concludes that the integration of spiritual parenting and the educational environment significantly contributes to the development of students’ emotional resilience and can serve as a reference for character-based education development.